Advances in telemedicine for health monitoring : technologies, design and applications - Rashid, Tarik A.; Chakraborty, Chinmay, 1984-; Fraser, Kym, 1958- (Healthcare technologies series ;, 2020)
This book has 14 Chapters: telemedicine development, implementation, and evaluation; surgical tele-mentoring; medical information processing technologies; healthcare signal/image processing techniques; real-time telemedicine ECG-processing platform; data mining in telemedicine; rural/remote community social work and tele-mental health services; technology-enhanced social work practice and education; advanced telemedicine system for remote healthcare monitoring; impact of tone-mapping operators and viewing devices on visual quality of experience of colour and grey-scale HDR images; modeling the relationships between changes in EEG features and subjective quality of HDR images; Internet of Medical Things (IoMT) and healthcare delivery in chronic diseases; transform domain robust watermarking method using Riesz wavelet transform for medical data security and medical data security and privacy; conclusion.